Modafinil and its structural analogs as atypical dopamine uptake inhibitors and potential medications for psychostimulant use disorder - Tanda, Gianluigi; Hersey, Melinda; Hempel, Briana; Xi, Zheng-Xiong; Newman, Amy Hauck (Current opinion in pharmacology, 2021)
[Display omitted] Pharmacotherapeutics for treatment of psychostimulant use disorder are still an unmet medical goal. Recently, off label use of modafinil (MOD), an approved medication for treatment of sleep disturbances, has been tested as a therapeutic for cocaine and methamphetamine use disorder. Positive results have been found in subjects dependent on psychostimulants without concurrent abuse of other substances. Novel structural analogs of MOD have been synthesized in the search for compounds with potentially broader therapeutic efficacy than the parent drug. In the present report we review their potential efficacy as treatments for psychostimulant abuse and dependence assessed in preclinical tests. Results from these preclinical proof of concept studies reveal that some modafinil analogs do not possess typical cocaine-like neurochemical and behavioral effects. Further, they might blunt the reinforcing effects of psychostimulants in animal models, suggesting their potential efficacy as pharmacotherapeutics for treatment of psychostimulant use disorders.